2013
DOI: 10.5772/56927
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of a Novel High-Power Series Elastic Actuator for a Lower Limb Robotic Orthosis

Abstract: A safe interaction is crucial in wearable robotics in general, while in assistive and rehabilitation applications, robots may also be required to minimally perturb physiological movements, ideally acting as perfectly transparent machines. The actuation system plays a central role because the expected performance, in terms of torque, speed and control bandwidth, must not be achieved at the expense of lightness and compactness. Actuators embedding compliant elements, such as series elastic actuators, can be desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…For its design, a systematic search of kinematically compatible planar solutions with 2 DOFs (topology level) was pursued [19], while the optimization of a selected topology (morphology level) was carried out to minimize actuation torques and forces parallel to the longitudinal axes of body segments, which can potentially damage articulations [20]. The robot comprises one pelvis brace (hosting joint A) and, for each leg, two rotary SEAs [18] actuating joints A and D, one thigh brace (hosting joint B) and one shank brace (hosting joint C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For its design, a systematic search of kinematically compatible planar solutions with 2 DOFs (topology level) was pursued [19], while the optimization of a selected topology (morphology level) was carried out to minimize actuation torques and forces parallel to the longitudinal axes of body segments, which can potentially damage articulations [20]. The robot comprises one pelvis brace (hosting joint A) and, for each leg, two rotary SEAs [18] actuating joints A and D, one thigh brace (hosting joint B) and one shank brace (hosting joint C).…”
Section: Methodsmentioning
confidence: 99%
“…at mechanical level) backrivability, can overcome the above-mentioned problems, even though it requires an extra effort in the mechanical design phase. The LENAR was purposively designed to exhibit reduced mechanical impedance by resorting to: i) compliant torsion elements in the actuated joints (Series Elastic Actuators, SEAs); ii) high efficiency in the gearmotors (to allow retrograde motion) [18]; iii) smart distribution of the inertia of the actuation apparatus; iv) lightweight design of robotic links.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, telerehabilitation can also benefit from the recent advancements of robot-aided rehabilitation, thus providing interactive, repetitive and task-specific activities that can be tailored to the user's needs, and promote motor learning, exploiting neuroplasticity, without the continuous oversight by a therapist. [5][6][7] Many studies have demonstrated the effective role of robots in upper limb robot-aided motor therapy; [8][9][10][11][12] conversely, a few studies have investigated the feasibility and the efficacy of remote robot-aided rehabilitation. [13][14][15][16] The concept of combining telerehabilitation and robot-assisted therapy represents a novel challenging approach in neurorehabilitation; such a concept shows the potential to provide cost-effective and consistently high-quality treatment to patients with limited access to rehabilitation clinics because of location or availability of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with an ordinary stiff actuator, the SEA has more advantages in following features, i.e., lower output impedance and back-drivability, shock tolerance, force transmission fidelity, storing and releasing energy, and passive impedance at high frequencies. Accoto et al presented a kind of SEA for a lower limb robotic orthosis, where a custom-made torsion spring with a stiffness of 272.25 Nm rad −1 is directly connected to the load and the delivered torque can be obtained by measuring the deflection of the spring through absolute encoders (Accoto et al, 2013). Several kinds of elastic springs in SEA were concluded and presented that linear springs and torsional springs were arranged in the transmission train actuators, where the discrete design details are described (Carpino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%